127k views
1 vote
Please Help!!!

Answer choices listed below...

What is a polynomial function in standard form with zeroes 1, 2, -3, and -1 ?

Please Help!!! Answer choices listed below... What is a polynomial function in standard-example-1

1 Answer

6 votes

Option A:


g(x) =x^4+x^3-7x^2-x+6

Solution:

Given data: Zeroes are 1, 2, –3, and –1.

To find the polynomial of the function for the given zeroes.

If 1 is a root of the polynomial then the factor is (x – 1).

If 2 is a root of the polynomial then the factor is (x – 2).

If –3 is a root of the polynomial then the factor is (x – (–3)) = (x + 3).

If –1 is a root of the polynomial then the factor is (x – (–1)) = (x + 1).

On multiplying the factors, we get the polynomial of the function.


\Rightarrow\ g(x)=(x-1)(x-2)(x+3)(x+1)


\Rightarrow\ \ \ \ \ \ \ \ =(x^2-2x-x+2)(x^2+x+3x+3)


\Rightarrow\ \ \ \ \ \ \ \ =(x^2-3x+2)(x^2+4x+3)

Now multiplying each term of the first factor by each term of the second.


\Rightarrow\ \ \ \ \ \ \ \ =x^2(x^2+4x+3)-3x(x^2+4x+3)+2(x^2+4x+3)


\Rightarrow\ \ \ \ \ \ \ \ =(x^4+4x^3+3x^2)+(-3x^3-12x^2-9x)+(2x^2+8x+6)

Removing brackets in each term.


\Rightarrow\ \ \ \ \ \ \ \ =x^4+4x^3+3x^2-3x^3-12x^2-9x+2x^2+8x+6

Combine the like terms and simplifying.


\Rightarrow\ \ \ \ \ \ \ \ =x^4+4x^3-3x^3+3x^2-12x^2+2x^2-9x+8x+6


\Rightarrow\ \ \ \ \ \ \ \ =x^4+x^3-7x^2-x+6


\Rightarrow \ g(x) =x^4+x^3-7x^2-x+6

Option A is the correct answer.

Hence
g(x) =x^4+x^3-7x^2-x+6.

User Eightball
by
5.3k points